(untitled) (Medico Legal Update, 2020)
Background: Caesarean section was first introduced to reduce the risks of normal delivery, and is recommended only when the lives of the mother and fetus are compromised, as it is associated with certain risks. However, some women’s perceptions may be influenced by local culture. According to international statistics , the rate of C-section is increasing globally, and in Iraq it is 2-3 times higher than other nations. More than 1/3 of women in Babylon choose C-section voluntarily, believing it is safer, healthier, and less painful. Aim of the Study: Identify the unexpected medical and surgical conditions of newborns by elective cesarean delivery in Al-Hillah city, and assess the association between the actual gestational age at birth and decision by which elective caesarean sections were done as influenced by local sociodemographic factors and perceptions; that resulted in those conditions. Methodology: This study is a cross sectional study conducted in Al-Hilla General Teaching Hospital from the beginning of March 2018 until the end on August 2018, and included a total of 150 neonates born via elective cesarean section who had unexpected medical and surgical conditions. Results: Mean maternal age was (26.27±9.56) year ranging from (16-43). Seventy percent of them had timing of < 39 weeks of gestation, and 36.7% had actual gestational age at birth of < 37 weeks. Almost half the them chose C-section for being safe. Respiratory compromise was the commonest medical complication among mothers. There was significant relationship between decision basis and actual gestational age at birth, as well as between maternal age and medical and surgical complications (P-value<0.05). Conclusion: Neonates born after elective cesarean delivery in Al-Hillah city have significantly higher rates of respiratory morbidity and longer length of hospital stay, with increased risk of certain medical and surgical complications. The unexpected medical complications are inversely related to gestational age at which elective cesarean section is timed.